Comunicação Segura e Confiável para Sistemas Multiagentes Adaptando Especificações XML - OLIVEIRA, Emerson José Santos (2006)
Multi-agent systems are evolving to enterprise applications and they are more used in open environments, such as the Internet. Many issues should be considered with this evolution, like security and reliability of communication. In this work, we propose a solution for secure communication and a solution for a reliable communication; both solutions are for multi-agent systems. These solutions adapt XML technologies and consist of several XML Specifications and RDF standard. For secure communication, we adapt the XML-DSig specification to provide integrity and digital signature; the XMLEnc specification is used to provide confidentiality through encryption, and the XKMS specification is used to provide PKI support. For reliable communication, we adapt the WS-RM specification that guarantees the message delivery. The RDF standard enables agents for exchanging messages using XML syntax. In this work, the tests with prototypes of the proposed solutions and comparisons with other solutions are also presented.